POLLEN MICROMORPHOLOGICAL TRAITS OF THE TYRRHENIAN STACHYS SALISII JORD. & FOURR. (LAMIACEAE) - Boi, M.; Lazzeri, V.; Bacchetta, G. (Annali di Botanica, 2013)
Pollen micromorphology of plants from four populations of the Tyrrhenian insular endemic Stachys salisii is examined using light and scanning electron microscopy. The preliminary results show some differences between the populations analyzed as regards pollen surface micromorphology and dimensions. The basic shape of the pollen grains is subprolate, usually tricolpate, but also oblate-spheroidal and tetracolpate. The pollen surface is microreticulate, perforate or foveolate. Lumina are separated by smooth or sinuate muri, which make them polygonal and elongate, while the number of punctae for each lumen also show some variations.